Pengaruh Harga, Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Konsumen Pada Tabularasa Cafe Jember - Pudhak Prasetiyorini; Sri Redjeki; Erika Dwi Pratiwi (Neolectura, 2023)
This study aims to analyze and determine the effect ofxprice, product quality andxservice quality on customer satisfaction at Tabularasa cafe Jember. From primary data obtained through questionnaires distributed to customers of Jember's Tabularasa cafe. The population in this study is not limited in number. In this study the sample used amounted to 96 respondents. This study uses 4 variables which are then analyzed using multiple linear regression analysis. From the results of the t-test research, the first hypothesis is that price (X1) has a significant effect on consumer satisfaction (Y) or H_1 is accepted because it is known that t_count is greater than t_table (1,949 > 1.660), in the second hypothesis, product quality (X2) has a significant effect on satisfaction. Consumer. (Y) or H_2 is accepted because it is known that t_count is greater than t_table (4,685 > 1,660), and in the third hypothesis, service quality (X3) has a significant effect on consumer satisfaction (Y) or H_3 is accepted because it is known that t_count is greater than t_table (2,315 > 1,660). And the value of Fcount is 94,431 with a significance value of 0.000. This shows that the value of Fcount is greater than Ftable 2.70 and the value of Sig is less than 0.05. Thus H0 is rejectedxand Ha is accepted. This means that the marketing mix consisting of price, product quality and service quality has a significant influence on consumer satisfaction at Tabularasa Cafe Jember.